2012
DOI: 10.3109/00016357.2011.645065
|View full text |Cite
|
Sign up to set email alerts
|

Oral habits in a group of consecutively treated orthodontic patients, using standardized video recordings for diagnosis

Abstract: Standardized video recordings improved the reliability of the recordings of the oral soft tissue dysfunctions. Their overall reduction after the end of orthodontic treatment coincided with a normalization of the sagittal skeletal and dental variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This prolonged habit could result in some medical and behavioural complications, such as intestinal parasitic infection, lead poisoning, digital deformity, paronychia or chronic hair pulling. Previous studies have also reported dental and maxillofacial sequelae of prolonged digit sucking, including anterior open bite, increased overjet, decreased overbite, protrusive incisors and a larger ANB angle which at times indicated the development of craniofacial deformity.…”
Section: Introductionmentioning
confidence: 99%
“…This prolonged habit could result in some medical and behavioural complications, such as intestinal parasitic infection, lead poisoning, digital deformity, paronychia or chronic hair pulling. Previous studies have also reported dental and maxillofacial sequelae of prolonged digit sucking, including anterior open bite, increased overjet, decreased overbite, protrusive incisors and a larger ANB angle which at times indicated the development of craniofacial deformity.…”
Section: Introductionmentioning
confidence: 99%